CONTROL OF FATTY ACID COMPOSITION IN PHOSPHOLIPIDS OF Escherichia coli: RESPONSE TO FATTY ACID SUPPLEMENTS IN A FATTY ACID AUXOTROPH - Esfahani, Mojtaba (1969)
The effect of exogenous unsaturated fatty acids on the fatty acid composition of phospholipids of a mutant of E. coli has been examined. These exogenous acids serve as growth factors for an auxotroph requiring unsaturated fatty acids. When each member of a structurally homologous series of cis-unsaturated fatty acids serves as a growth factor, the percentage of unsaturated fatty acid present in phospholipids increases with increasing chain length or decreasing number of double bonds in the apolar chain of the supplement. At 37°, trans-octadecenoic acids support growth and are incorporated into phospholipids at levels higher than the corresponding cis-acids. However, a temperature shift to 27° with trans-acids results in loss of viability and lysis. Utilization of cis-acids as supplements at decreasing temperatures between 42° and 27° results in increasing amounts of unsaturated fatty acids in phospholipids with decreasing temperature. These observations suggest the operation of a regulatory mechanism which controls the composition of saturated versus unsaturated acids in order to maintain the physical properties of phospholipids within narrow limits.